The role of physiotherapy in fibromyalgia: Current and future perspectives - Antunes, Mateus Dias; Marques, Amélia Pasqual (Frontiers in Physiology, 2022)
Fibromyalgia is a chronic pain condition characterized by generalized musculoskeletal pain, hyperalgesia and allodynia, commonly associated with other symptoms such as fatigue, poor sleep quality, anxiety and depression. The clinical manifestations of this rheumatic disease have significant psychosocial and economic repercussions, with a substantial impact on health status, quality of life and social activities. Currently, recommendations for the management of fibromyalgia include patient education and non-pharmacological interventions, and among the indicated treatments, clinical guidelines include physical therapy, essential for individuals suffering from this disease. Research in the physiotherapy field has demonstrated its effectiveness, but there is a need to update the literature. This study aims to identify the effectiveness of physical therapy in the treatment of individuals with fibromyalgia. The effects of physical therapy interventions are summarized in order to provide a reference for future research and clinical application. Research on non-pharmacological physical therapy-oriented treatments has grown in recent years as an alternative for fibromyalgia treatment. We hope that this review will allow fibromyalgia patients in different conditions to receive appropriate physical therapy interventions and provide a reference for healthcare professionals, especially physical therapists, interested in the current treatment and future research on non-pharmacological treatments for fibromyalgia.